Added Qualities of New Interventions within the Historic Built Environment - Kudumoviç, Lana; Yıldırım, İnanç Işıl (Sveuciliste Josipa Jurja Strossmayera u Osijeku, 2023)
Contemporary architecture, within the historic urban settings, is acquired as the contribution of the current time to a particular existing ambience, whereas new interventions are expected to be significant authorship achievements. This paper discusses the new qualities within the historic urban fabric produced by the contemporary interventions, in particular, those of balanced contrast. Such new spatial contributions may be applied on different levels (ambience (urban), object and detail), while each of them is expected to produce added qualities. Built on different theories about space qualities and characteristics, this paper evaluates selected examples by distinguishing three major groups of produced qualities (physical, economic and socio-cultural). This paper also suggests balanced contrast applied to new interventions within the valuable historic ambience as an acceptable approach. Finally, the correlation of all comprising elements of the newly design objects with the surroundings is emphasised to be important in producing new values.
Keywords: Balanced Contrast; Contemporary Upgradesties; Historic Environment; New Architecture; Space Qualities